DISCOURSE DISFLUENCIES IN BILINGUAL COURT HEARINGS - TORSTENSSON, Niklas; GAWRONSKA, Barbara (Comparative Legilinguistics, 2009)
In about 9% civil and criminal cases that are settled in Swedish District courts every year, i.e. in roughly 10 000 court hearings, an interpreter is employed when at least one of the involved parties speaks another language than Swedish. In this paper, aspects of interpretation in the courtroom are discussed in general, and examples from court proceedings are used to analyse disfluent situations. The role of the interpreter is viewed, and compared to that of other participants’ in the discourse. Aspects of legal rights for the individual are discussed in relation to examples from other language communities. The results show that the confusing situations and misinterpretations are not only dependent on the decisions made by the interpreter. The attitudes and the linguistic behaviour of all discourse participants may contribute to the disfluencies.